Brain MRI features and scoring of leukodystrophy in adult-onset Krabbe disease. (13th August 2019) - Cousyn, Louis; Law-Ye, Bruno; Pyatigorskaya, Nadya; Debs, Rabab; Froissart, Roseline; Piraud, Monique; Federico, Antonio; Salvatore, Simona; Cerase, Alfonso; Macário, Maria C.; Durães, João; Kim, Seung H.; et al.
Abstract : Objective: To perform a systematic analysis and scoring of brain MRI white matter hyperintensities (WMH) in adult-onset Krabbe disease. Methods: We retrospectively collected basic clinical data and the first available brain MRI from patients with confirmed Krabbe disease with first clinical manifestations beyond 10 years of age. Data were obtained from our reference center for lysosomal diseases (n = 6) and from contacted authors of published articles describing patients with adult-onset Krabbe disease (n = 15). T2-weighted fluid-attenuated inversion recovery images of each patient were analyzed and scored using a radiologic score of WMH in a single center. Results: The corticospinal tract was always affected by WMH (100% of patients), however, with some distinctions along the tract: the precentral gyrus (100%), corona radiata (95%), and posterior internal capsule (81%) were highly abnormal, whereas the mesencephalon (57%), pons (52%), and medulla oblongata (5%) were less affected. WMH were also frequently present in the posterior lateral periventricular white matter (95%), optic radiations (86%), postcentral gyrus (71%), medial lemniscus (62%), and corpus callosum, especially in the isthmus (71%), whereas the genu was always normal. A few patients did not have the classical MRI pattern but extensive hyperintensities (n = 3), or patchy distribution of hyperintensities mimicking an acquired etiology (n = 2), or very subtle hyperintensities of the corticospinal tract (n = 1). Conclusions: We specified the main locations of WMH, which were observed in the earliest stages of the disease and were also present in patients with atypical MRI pattern, highlighting the importance of radiologic features to guide the diagnosis.